Basic guide to dental instruments - Scheller-Sheridan, Carmen (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
'Basic Guide to Dental Instruments provides a working inventory of dental instrumentation in common use in dental surgeries. A clear photograph of each class and many varieties of instrument is included, and then described according to the following principles: name, usage, any relevant features and varieties. Each section is dedicated to a specific discipline or division of dentistry. Complete set-ups have been included at the end of most sections for various procedures. The coverage reflects instrumentation and accessory items used in general dental practice, routine hospital dental procedures and selected specialist settings. The author adopts a flexible approach which recognises that some instruments are multi-functional, and their names and usage can vary across dental surgeries. This approach, coupled with the range of instruments covered, makes the book an ideal'portable' resource across general practice, hospital and a range of specialist settings. The book also highlights instruments which can be easily confused. In addition to detailing the classic sets of dental instruments, the importance of instrument care and sterilisation regimes is acknowledged'--Provided by publisher.
Infection control in the dental surgery -- Dental radiography -- Basic instruments -- Instruments and sundries used in moisture control -- Local anaesthesia -- Instruments used for rubber dam placement -- Handpieces, burs, and rotary attachments -- Instruments used in basic restorative procedures -- Matrix bands and matrix retainers -- Instruments used in endodontic treatment -- Elevators -- Extraction forceps -- Surgical instruments -- Measuring devices -- Impression trays -- Orthodontic instruments -- Instruments used in periodontal procedures -- Instruments used in removable and fixed prosthodontics.
Includes bibliographical references and index.
Keywords: Dental Instruments -- Handbooks